2022
DOI: 10.3390/plants11030373
|View full text |Cite
|
Sign up to set email alerts
|

QTL Identification for Stem Fiber, Strength and Rot Resistance in a DH Population from an Alien Introgression of Brassica napus

Abstract: Stem fiber, stem strength and stem-rot resistance are important agronomic traits in Brassica napus. To understand the molecular mechanism that controls the stem-related traits, we investigated the stem lignin (ADL), cellulose (Cel), hemicellulose (Hem) content, S/G monolignol ratio (SG), stem breaking force (BF), breaking strength (F) and Sclerotinia sclerotiorum resistance (SSR). Each trait was significantly positively or negatively correlated with more than three of the other six traits. QTL mapping for ADL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…In this study, the S3307 treatment significantly increased the dry weight of the stem, leaf, pod, and whole plant (Figure 3). The deposition of structural carbohydrates (i.e., lignin, cellulose, hemicellulose) can lead to thicker stem tissue [45], affecting the elastic modulus of the stem and thus affecting its bending strength [46,47]. Zheng et al [10] and Hussain et al [45] believed that the content of lignin and cellulose in basal internodes was positively correlated with the lodging resistance of stems.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the S3307 treatment significantly increased the dry weight of the stem, leaf, pod, and whole plant (Figure 3). The deposition of structural carbohydrates (i.e., lignin, cellulose, hemicellulose) can lead to thicker stem tissue [45], affecting the elastic modulus of the stem and thus affecting its bending strength [46,47]. Zheng et al [10] and Hussain et al [45] believed that the content of lignin and cellulose in basal internodes was positively correlated with the lodging resistance of stems.…”
Section: Discussionmentioning
confidence: 99%
“…28,[41][42][43] Lignin, cellulose, hemicellulose and chitin are known to impact the elastic modulus, therefore affecting the flexural rigidity of the basal stem. 44,45 Silicon is an important structural component related to stem strength, and the application of silicon could increase the content of lignin in sclerenchyma cells, consequently improving stem strength in OSR crops. 46 Further studies should investigate cell wall structure in crops affected by CSFB to understand whether increased lodging risk is related to both physiological and biochemical changes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified relationships between root characteristics and lodging risk. 26,[43][44][45][46][47][48] To understand the potential impact of CSFB on root anchorage further, inoculation experiments with different larval populations could be used to measure the impact of larvae on rooting traits.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this strategy, a large difference in the SSR resistance level is the main criterion for selecting parents, and backbone breeding parents that have undergone natural selection and strict artificial selection are rarely used as susceptible parents because their SSR resistance levels are not low enough. Using this strategy, numerous researchers have applied various methods for detecting SSR to discover a large number of SSR resistance-related QTLs in different growth stages of rapeseed ( Zhao et al., 2006 ; Yin et al., 2009 ; Mei et al., 2013 ; Wu et al., 2013 ; Li et al., 2015 ; Wei et al., 2016 ; Wu et al., 2016a ; Shao et al., 2022 ). However, the correlation between the results of different identification methods was low, as was the repeatability of QTLs mined in different studies; therefore, few or no QTLs have been applied to improve resistance to SSR ( Ding et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…SSR resistance in rapeseed is related to the stem strength ( Shao et al., 2022 ), lignin content ( Cao et al., 2022 ), glucosinolate content ( Zhao and Meng, 2008 ), FT ( Wei et al., 2014 ; Wu et al., 2019 ; Zhang et al., 2019 ), and other traits ( Feng et al., 2021 ), and their interactions should be monitored during the improvement of SSR resistance. A study of the FT and SSR resistance of 521 rapeseed inbred lines revealed a significant negative correlation between the two traits, demonstrating that they had the closest relationship.…”
Section: Introductionmentioning
confidence: 99%